Physicochemical characterization and in vitro digestibility of resistant starch from corn starch sugar residue - Qianqian Dai; Xiaoke Li; Chuanbo He; Ying Liang; Hejian Xiong; Ying Ma; Shaowei Zhai (Food Chemistry: X, 2025)
This study sought to investigate the thermal stability and digestibility of corn starch sugar residue resistant starch (CSSR-RS) through comparative analysis of the physicochemical properties and structural characteristics among CSSR-RS, high-amylose corn starch (HS), and normal corn starch (NS). CSSR-RS contained 51.76 % resistant starch (RS), with 42.6 % remaining after high-temperature treatment, which was significantly higher than HS, demonstrating strong resistance to gelatinization. CSSR-RS is characterized by highly ordered aggregation of small molecules with a C-type crystalline structure, and irregular granular structures with wrinkled surfaces. Compared with NS and HS, the short-range and long-range order of CSSR-RS were significantly higher, indicating excellent thermal stability. In vitro simulated digestion revealed that the total hydrolysis rate of CSSR-RS was significantly lower than those of NS and HS, and the residual digesta of CSSR-RS also showed better resistance to digestion than HS. CSSR-RS exhibited significant development prospects in healthy food.